PENGARUH PERENCANAAN, PELAKSANAAN, PENATAUSAHAAN, DALAM LAPORAN PERTANGGUNGJAWABAN KEUANGAN DANA DESA TERHADAP REALISASI PENGELOLAAN APBDes (Studi Kasus Pada Kecamatan Mojogedang, Kabupaten Karanganyar) - Ningsih, Rahayu Mulya; Suharno, Suharno; Harimurti, Fadjar (Universitas Slamet Riyadi, 2021)
This study to examine and analyze the effect of planning, implementation,administration in the financial accountability report of village funds on therealization of village income and expenditure budget management. Thepopulation in this study is community elements involved in the management of theVillage Income and Expenditure Budget throughout the Mojogedang District. Thissampling method uses census samples or saturated samples. The data analysistechnique used is descriptive test, validity test, reliability test, multiple linearregression hypothesis test, classical assumption test, t test, F test, and coefficientof determination test. The results of this study have no significant effect betweenplanning and realization of fund management. village. Implementation does nothave a significant effect on the realization of village fund management.Administration has a significant effect on the realization of village fundmanagement.